Research on friction and wear behavior of gradient nano-structured 40Cr steel induced by high frequency impacting and rolling. (January 2018) - Zhao, Xiaohui; Zhao, Bo; Liu, Yu; Cai, Yu; Hu, Chunhua
Abstract: Surface gradient nanostructure of 40Cr steel was prepared by using high frequency impacting and rolling. First, surface nanocrystallization mechanism was investigated through surface morphology, microstructure evolution, work hardening and residual stress. Then friction and wear mechanism of gradient nanostructured 40Cr steel was discussed by coefficient of friction, wear mass loss and worn morphology. Grain refinement process through formation of dislocation tangles, transformation of sub-grains to nanocrystals and the breakage phenomenon of the laminated structure of pearlite during high frequency impacting and rolling treatment are considered as the surface nanocrystallization mechanism. The wear mass loss of gradient nanostructured surface is far below as-received surface as the increase of applied load. The friction and wear mechanism of as-received 40Cr steel was changed from abrasive wear to fatigue wear, while fatigue wear of the gradient nanostructured 40Cr steel was not presented as the increase of applied load (10 N–50 N). Highlights: Surface gradient nanostructure of 40Cr steel was prepared by using high frequency impacting and rolling. Nanocrystallization mechanism of 40Cr steel was studied through microstructure, work hardening and residual stress. Wear mechanism of nanostructured 40Cr steel was discussed by friction coefficient, wear mass loss and worn morphology.